2018
DOI: 10.1111/cen3.12470
|View full text |Cite
|
Sign up to set email alerts
|

Severe rebound relapse of multiple sclerosis after switching from fingolimod to dimethyl fumarate

Abstract: Background Dimethyl fumarate (DMF) was the second oral disease-modifying drug to be approved for multiple sclerosis (MS) in Japan, after fingolimod. Switching from fingolimod to DMF treatment is becoming increasingly common, because DMF has shown a better risk-benefit profile and an equivalent efficacy to fingolimod. Case presentation We report a 35-year-old woman who was positive for anti-John Cunningham virus antibody and who developed severe rebound relapse of MS after switching from fingolimod to DMF. Five… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…This was an unexpected experience as DMF is an oral drug with an equivalent efficacy to fingolimod [21,22]. Other authors have reported a similar experience with this transition strategy [9,23]. It is likely that several immunopathogenic mechanisms are involved in MS disease reactivation after fingolimod cessation.…”
Section: Discussionmentioning
confidence: 79%
“…This was an unexpected experience as DMF is an oral drug with an equivalent efficacy to fingolimod [21,22]. Other authors have reported a similar experience with this transition strategy [9,23]. It is likely that several immunopathogenic mechanisms are involved in MS disease reactivation after fingolimod cessation.…”
Section: Discussionmentioning
confidence: 79%